Analysis of demand for dairy products and the application of a spatial equilibrium model to the pasteurized milk market in Honduras: some estimates of the impact of DR-CAFTA - García Oliva, Norman F. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2008